Not Just Red and White: Wine Expertise Influences Wine Color Descriptions - Reinhartz, Alice (Student Undergraduate Research E-journal!, 2016)
The linguistic relativity debate has often focused on how languages differ in the coding of sensory perceptions. Sensory expertise of some cultures possibly increases the consistency of their language’s sensory coding. To analyze the effects of sensory expertise within cultures, wine experts and non-experts were tested in color naming and categorization in a neutral and expert context. Wine expertise influenced color naming in both contexts, but not categorization. Experts decreased in consistency while using more specific color terms. This shows that expertise can influence language and that verbal and non-verbal domains are affected differently.